The Settlement Behavior Using Replacement Embankment with Mortar Foam and Geofoam using LISA FEA - Aco Wahyudi Efendi (Nusantara Civil Engineering Journal, 2023)
The IKN area, especially in the dock and stockyard construction area, is in an area with soft surface soil and requires several options for handling the stockyard area with several materials that are being widely used and easy methods and provide economic value in development. The use of geoform can increase the CBR value of native soil and the use of geofoam as embankment material provides a higher safety factor value with a smaller deformation value besides that the foam mortar material contributes to a small decrease and stress on the surface of the native soil. This study provides a behavioral review of the vertical settlement and stresses that occur in the soil and gives special behavior to the Geofoam material in the presence of hydrostatic forces. The largest settlement that occurred was 0.0961 m on the surface of the foam mortar, while on the existing soil surface a settlement of 0.0288 m occurred, while the largest settlement that occurred was 0.04254 m on the surface of the geofoam, while on the existing soil surface a settlement of 0.0277 m occurred.